Smart Governance of City’s Culture: Theoretical and Empirical Aspects - Milkintas, Rytis (Socialiniai tyrimai, 2020)
The goal of the research is to prepare a theoretical model of smart cultural governance and to evaluate the smart cultural management of Šiauliai city according to it. The background of creating a smart culture governance model is to define the theoretical constructs of smart city and smart culture management by looking for correlations between these concepts in order to closely link cultural management with the implementation of cultural policy in city management processes and to highlight the specifics of smart cultural management. A systematic model of a smart city is formed and presented, of which cultural management is an integral part. The model highlights the links between cultural management and other dimensions of the smart city. The theoretical model of smart culture management, which was adapted to investigate the expression of smart culture management in Šiauliai city, is presented. This kind of research has not been done so far in analyzing smart culture management in Šiauliai city. The need for the research was inspired by culture specialists of Šiauliai City Municipality Administration and heads of cultural institutions. The qualitative content analysis of theoretical sources of foreign countries and Lithuania was conducted as well as in-depth interviews to collect information that was processed through qualitative content analysis and systematized using matrices. The assessment of model expression based on the informants’ attitudes enabled the researcher to draw substantive conclusions. The research is relevant to Šiauliai city culture field institutions (private, subordinate municipality, subordinate to the Ministry of Culture of the Republic of Lithuania), Šiauliai city culture field policymakers. In a broader sense, the improvement in the quality of the intelligent social system highlighted in the study will significantly contribute to the general level of culture in Šiauliai. These positive changes will be experienced by the recipients of cultural services. Further research in the field of smart city cultural management is planned to analyze not only the situation of Šiauliai city but also the cultural field of Lithuania as a whole, in connection with the practices of the international cultural field. It is planned to study the smoothness of the transformation of cultural field institutions, adaptation to smart cultural management, and the emerging challenges. Further research is planned to analyze the scientific studies prepared by smart cities, to look for specific actions highlighted in them, challenges for the cultural sector in adapting to the gradual transformation of cities into smart cities.